Five portraits of women for soprano, solo horn and large ensemble : (2012) : [op. 100] - Sallinen, Aulis 1935-; Haavikko, Paavo 1931-2008 (Novello, 2013)
Five portraits of women is a set of songs with large ensemble derived by Aulis Sallinen from arias from three of his operas: The Red Line, The king goes forth to France, and Kullervo. Each draws a portrait of a woman compelled in her role by fate or a mission. The vocal lines differ only very slightly from their original counterparts in the operas but the revised orchestral accompaniment creates an extraordinary new soundscape as background to the arias, consisting as it does of a woodwind orchestra, four cellos, a harp and a piano. There is also a solo French horn which acts as a sort of masculine counterweight to the female vocalist. Five portraits of women was commissioned by the Finnish Radio Symphony Orchestra.--Music Sales WWW site
Text by Aulis Sallinen and Paavo Haavikko; English translation by Stephen Oliver and Adam Pollock. - Duration: approximately 25:00
Keywords: Songs (High voice) with instrumental ensemble / Scores; Haavikko, Paavo / Musical settings; Sallinen, Aulis / Musical settings; Songs; Art music; Scores